ANALYSIS OF LEGAL DISPARITIES BETWEEN TYPES OF CREDITORS IN THE SETTLEMENT OF BANKRUPT ASSETS: A STUDY OF THE DECISION IN CASE NO. 37/PDT.SUS-PKPU/2023/PN.NIAGA SEMARANG - Asmah, Asmah; N.S, Shinta; Jaya L., Ricky Khayat (International Journal of Multidisciplinary Research and Literature, 2025)
In the bankruptcy process to resolve the problem of the debtor's inability to fulfill its debt obligations to creditors in full, complex dynamics arise between the interests of the creditors. Settlement through bankruptcy cannot guarantee the fulfillment of all creditors' rights and allows for inequality experienced by some creditors. This study aims to determine the factors causing inequality or disparity in legal treatment for separated, preferred. Concurrent creditors settle bankrupt assets based on court practice and choose to improve the formulation of bankruptcy law in Indonesia to ensure justice and legal certainty for all types of creditors in settling the assets of bankrupt debtors. This study uses a normative juridical research method, namely a kind of research that focuses on examining the application of rules or norms in applicable law. The results show concurrent creditors do not receive their rights as they should in bankruptcy settlement. The curator prioritizes creditors with privileged and priority rights, such as preferred and secured creditors, in settling bankruptcy assets. Furthermore, the bankruptcy law must be updated with policies to resolve debt issues that protect creditors in settling debtor obligations based on justice and legal certainty.